2022
DOI: 10.1155/2022/4791059
|View full text |Cite
|
Sign up to set email alerts
|

miR-199a-5p Plays a Pivotal Role on Wound Healing via Suppressing VEGFA and ROCK1 in Diabetic Ulcer Foot

Abstract: Diabetes mellitus (DM) is a growing health problem. As a common complication of DM, diabetic foot ulcer (DFU) results in delayed wound healing and is a leading cause of nontraumatic amputation. miR-199a-5p, a short noncoding RNA, had abnormal expression in DFU wound tissues. The expression of miR-199a-5p was significantly increased in DFU wound tissues, skin tissues of diabetic rats, and high glucose-induced cells. Vascular endothelial growth factor A (VEGFA) and Rho-associated kinase 1 (ROCK1) are directly ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Several studies have confrmed that many miRNAs participate in the process of wound healing [26][27][28][29]. During the infammatory period of the wound, miRNA-181c and miRNA-21-5p promote the expression of M2 macrophages to inhibit the infammatory response and shorten the infammatory response time [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confrmed that many miRNAs participate in the process of wound healing [26][27][28][29]. During the infammatory period of the wound, miRNA-181c and miRNA-21-5p promote the expression of M2 macrophages to inhibit the infammatory response and shorten the infammatory response time [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…By directly targeting VEGFA and Rho-associated kinase 1 (ROCK1), it leads to decreased proliferation and migration of ECs. 46 In diabetic rats, inhibition of miR-199a-5p significantly increased the expression of VEGFA and ROCK1, thus promoting wound healing. Therefore, miR-199a-5p and its targets have a significant therapeutic effect on diabetic wounds.…”
Section: Abnormally Expressed Mirs In the Woundmentioning
confidence: 99%
“…Therefore, miR-199a-5p and its targets have a significant therapeutic effect on diabetic wounds. 46 Compared with normal mice, miR-31-5p was significantly reduced in the full-thickness wound of diabetic mice, and its target HIF1AN was inadequate, which led to the deficiency of EC proliferation, migration, and tube formation. 38 By using milk exosomes loaded with miR-31-5p mimics, the research team effectively improved the function of ECs in vitro and also promoted wound blood vessel formation and wound healing in this way.…”
Section: Abnormally Expressed Mirs In the Woundmentioning
confidence: 99%
“…Huang et al [ 47 ] found that miR-489-3p downregulation increases sirtuin (SIRT) 1 expression, promotes the PI3K/AKT/eNOS signaling pathway, improves cellular antioxidant capacity, and alleviates DFU. MiR-199a-5p has an important role in the development of diabetes and its complications[ 48 , 49 ]. Moreover, miR-199a-5p promotes apoptosis and ROS production within pancreatic β-cells in type 2 DM (T2DM)[ 50 ].…”
Section: Mirnasmentioning
confidence: 99%
“…MiR-199a-5p sponge-adsorbed to hsa-circ-006040 inhibits macrophage-mediated inflammatory responses in type 1 DM (T1DM)[ 48 ]. Wang et al [ 49 ] found that downregulating miR-199a-3p in endothelial cells alleviates inhibition of the target VEGFA and Rho-related kinase 1, rescuing the cellular damage induced by high glucose and restoring angiogenic function. Therefore, these findings suggest that regulating miRNA expression during the proliferative phase of wound healing has great potential in DFU treatment and wound repair.…”
Section: Mirnasmentioning
confidence: 99%